Application of Knowledge Management System for Cattle Cultivation - Kusnadi, Edi; Yanitasari, Yessy; Supriyadi, Supriyadi (ILKOM Jurnal Ilmiah, 2021)
Cow are family animal bovinae and subfamily bovidae. Cow are raise for use in meat and milk. Beef production does not fullfill National beef demand. This is influenced by several factors, one of them is the cultivation pattern. But knowledge about cultivation is still scattered and unstructured. Knowledge Management System (KMS) offer a knowledge system that can be used to create, collect, store, maintain and disseminate knowledge. In this study KMS has been applied to cattle farming with the Knowledge Management System Life Cycle (KMSLC) method. The outcome of the research is a web based application regarding the management of cattle farming that have been tested by experts and users with an average test results stated good. The features of this KMS application are knowledge capture, knowledge sharing and knowledge application system, so they can share knowledge between one user and another. In addition, this application is equipped with a discussion forum that serves as a place to interact between fellow users or with experts.